In vitro exploration of drug-induced thrombotic microangiopathies: clues of diverse endothelial activation pathways respective to interferon-β1a, ciclosporin A, and gemcitabine exposure - Cubilier, Edouard; Taghavi, Maxime; De Prez, Eric; Jacobs, Lucas; Sinaeve, Sébastien; Nortier, Joëlle; Antoine, Marie-Hélène (Frontiers in Pharmacology, 2026)
Pro-inflammatory and pro-thrombotic stimuli can activate endothelial cells (ECs) and predispose them to thrombotic microangiopathies (TMAs). Drug-induced TMA (DITMA) may occur in clinical practice during treatment with interferon-β1a (IFN-β1a), ciclosporin A (CsA), and gemcitabine (GEM). DITMA may also trigger the complement system and induce membrane attack complex (MAC, C5b-9) deposition in vivo, although their role and the benefit of inhibition remain unclear. In an experimental in vitro model of microvascular ECs exposed to these three drugs, we searched for MAC deposits and drug-specific pro-inflammatory and pro-thrombotic traits to gain insights into the mechanisms potentially involved in DITMA. Human microvascular endothelial cells line-1 (HMEC-1) was treated with 10% normal human serum, CsA, GEM, and IFN-β1a. Cell viability for each drug was measured using the resazurin assay. Cell component expression of the following markers involved in endothelial pathogenic activation was measured via immunofluorescence and flow cytometry: C5b-9, interleukin (IL)-1α, IL-6, E-selectin, platelet EC adhesion molecule-1 (PECAM-1), intercellular adhesion molecule-1 (ICAM-1), and von Willebrand factor (vWF). Levels of plasminogen activator inhibitor-1 (PAI-1) and urokinase plasminogen activator (uPA) were measured in the supernatants using the enzyme-linked immunosorbent assay (ELISA). Significantly increased C5b-9 deposits were found with each drug, and increased drug-specific activation marker expressions appeared in HMEC-1s when exposed to CsA (IL-1α, IL-6, ICAM-1, E-selectin, vWF, and uPA), GEM (IL-1α, IL-6, PECAM-1, ICAM-1, E-selectin, and vWF), and IFN-β1a (PECAM-1, ICAM-1, PAI-1, and uPA). Each drug induces MAC deposits on HMEC-1s and singular endothelial activation profiles, potentially leading to thrombogenesis observed in DITMA.